Desenvolvimento de metodologias de análises residuográficas de interesse forense utilizando folhas de grafite e eletrodos impressos em 3D como amostradores/sensores eletroquímicos - Castro, Silvia Vaz Fernandes (2022)
This work describes the development of analytical procedures for the analysis of residues commonly found in crime scenes, such as gunshot residue (GSR) and explosives, using electrochemical techniques associated with graphite sheet (GS) and 3Dprinted electrodes. These electrodes were chosen with the objective of also acting directly as collectors in samples containing these types of residues. In the first part of the work, the use of graphite sheet (GS) as a new platform for the collection and detection of explosives is demonstrated, especially due to the characteristics of this material, such as lightness, high electrical conductivity and flexibility. The method was first demonstrated for the determination of the explosive 2,4,6trinitrotoluene (TNT), using squarewave voltammetry (SWV) as a technique and, posteriorly, the sequential determination of the explosives hexahydro1,3,5trinitro1,3,5triazine (RDX) and TNT has also been demonstrated using stripping voltammetric techniques. All analytical parameters were determined in solution, obtaining wide linear ranges and low value of limit of detection, and the collection step was performed through the direct contact of GS with surfaces previously contaminated with residues of explosives. The results obtained demonstrate that the proposed methodologies allowed the collection of analytes in the order of nanograms, evidencing that the stripping techniques were able to considerably improve detection sensitivity, which shows the potential of GS in analyses involving the use of explosives. In the second part of the work, the use of 3D printing technology is demonstrated for the construction of working electrodes using conductive filaments composed of graphene and polylactic acid (G/PLA) for the collection and detection of metals found in GSR samples. For this, the technique of squarewave anodic stripping voltammetric for the simultaneous determination of Pb2+ and Sb3+, in solution, and posteriorly the performance as a collector was evaluated in the sampling step carried out through direct contact of the sensor with the hands of individuals who had performed the shots. An excellent performance was evidenced and it was possible to identify the metals present in the collected material. The use of the 3D pen for the development of devices aimed at this type of analysis was also demonstrated, especially with the aim of optimizing the collection step and improving the sensitivity of the method, showing that 3D printed electrodes are excellent candidates for forensic analysis.